2016
DOI: 10.1001/jamacardio.2016.0263
|View full text |Cite
|
Sign up to set email alerts
|

Association of Coronary Stenosis and Plaque Morphology With Fractional Flow Reserve and Outcomes

Abstract: Having a normal FFR requires unimpaired vasoregulatory ability and significant luminal stenosis. Therefore, FFR should identify lesions that are unlikely to possess large necrotic core, rendering them safe for treatment with medical therapy alone. Further studies are warranted to determine whether revascularization decisions in patients with stable coronary artery disease could be improved by assessment of both plaque composition and ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(69 citation statements)
references
References 32 publications
5
59
1
2
Order By: Relevance
“…Alternatively, the authors propose that coronary microvascular dysfunction (in the absence of obstructive coronary artery disease) may be operational and would be more prevalent among hypertensive, dyslipidemia, and diabetic patients. 5 Thus, discordance would occur with physiological abnormalities or ischemia without a high-grade stenosis along with stenosis without ischemia, as previously described by Ahmadi et al 3 Data from positron emission tomography imaging support the independent prognostic significance of reduced coronary flow reserve even among patients with nonobstructive coronary artery disease. 6 Although there are differences between positron emission tomography and invasive physiological measures, these data underscore the complexity of clinical care and the limitations of management based on anatomic data alone.…”
Section: See Article By Adjedj Et Alsupporting
confidence: 62%
“…Alternatively, the authors propose that coronary microvascular dysfunction (in the absence of obstructive coronary artery disease) may be operational and would be more prevalent among hypertensive, dyslipidemia, and diabetic patients. 5 Thus, discordance would occur with physiological abnormalities or ischemia without a high-grade stenosis along with stenosis without ischemia, as previously described by Ahmadi et al 3 Data from positron emission tomography imaging support the independent prognostic significance of reduced coronary flow reserve even among patients with nonobstructive coronary artery disease. 6 Although there are differences between positron emission tomography and invasive physiological measures, these data underscore the complexity of clinical care and the limitations of management based on anatomic data alone.…”
Section: See Article By Adjedj Et Alsupporting
confidence: 62%
“…However, given the substantial population of patients showing FFR within the gray zone ranging from 0.75 to 0.80 in the reverse mismatch group, superiority of PCI for those lesions may deserve further consideration 34. Previous studies have suggested the impact of plaque characteristics on FFR values for a given anatomical stenosis in an epicardial coronary artery 35. The present study reports the association of CFR and IMR with FFR.…”
Section: Discussionmentioning
confidence: 72%
“…101 This may explain why FFR-negative lesions are safe to defer to medical therapy despite a significant degree of luminal narrowing; a 0.2% 2-year rate of MI arising from FFR-negative lesions was observed in the FAME study despite 104 lesions having 70% to 90% luminal narrowing. 10,101 A related intriguing question that needs to be addressed is whether all FFR-positive plaques have the same prognosis, and thus do all require revascularization? Based on the FAME 2 data, only 8.2% of FFR-positive plaques that were randomized to medical therapy resulted in death or MI within 2 years.…”
Section: Discussionmentioning
confidence: 98%
“…47 Although some severely stenotic lesions may not result in detectable ischemia (stenosis without ischemia), others with only a mild-moderate degree of angiographic stenosis may result in ischemia (ischemia without stenosis). 100,101 Features other than the degree of luminal stenosis, such as lesion length, entrance angle, exit angle, size of the reference vessel, and absolute flow relative to the territory supplied, are important in determining FFR-verified lesion-specific ischemia 50 and might explain the discordance between anatomy and physiology in some cases. Recently, it has been shown that the presence of high-risk plaque features, especially large low attenuation plaque, a CTA surrogate for necrotic core, is strong predictor of FFR-verified ischemia independent of degree of luminal stenosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation